2015
DOI: 10.1038/eye.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell loss and complication rates with combined Descemets stripping endothelial keratoplasty and cataract surgery in a UK centre

Abstract: Purpose To report 6-month, 1-and 2-year endothelial cell loss (ECL), intra-and postoperative complications in a large series of patients undergoing either Descemets stripping endothelial keratoplasty (DSEK) or a combined phacoemulsification and DSEK in a UK centre. Patients and methods Patients undergoing DSEK with or without concurrent cataract surgery were included in this retrospective study. Surgeries were performed between January 2006 and May 2013. Main outcomes included intra-and postoperative complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The complication rate and postoperative ECD for triple procedures compared to the DSAEK alone cases have not been shown to be different for short-term periods (6 months and 12 months) or longer-term follow-up of 3 to 5 years. [ 12 14 ] The 5 year ECL in our study (44.4%) was comparable to the 3 year ECL in the CPTS for the Fuchs dystrophy subgroup (44%). [ 12 ] The Price et al study reported a higher 5 year ECL at 53% compared to our study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The complication rate and postoperative ECD for triple procedures compared to the DSAEK alone cases have not been shown to be different for short-term periods (6 months and 12 months) or longer-term follow-up of 3 to 5 years. [ 12 14 ] The 5 year ECL in our study (44.4%) was comparable to the 3 year ECL in the CPTS for the Fuchs dystrophy subgroup (44%). [ 12 ] The Price et al study reported a higher 5 year ECL at 53% compared to our study.…”
Section: Discussionsupporting
confidence: 65%
“…[ 9 , 10 ] However, there is a theoretical risk that the greater instability of the newly placed intraocular lens (IOL) in a triple procedure and the added postoperative inflammation from the concomitant cataract surgery may increase the endothelial cell loss rate in a triple procedure graft v a DSAEK without other simultaneous surgery. [ 11 ] While the Cornea Preservation Time Study [ 12 ] (CPTS) and other single center studies [ 13 , 14 ] did not show a significant difference in endothelial cell loss of Triples v DSAEK alone, the study presented here has a longer postoperative time frame than the CPTS and more patients to analyze for the 5 year postoperative visit than any prior single center study.…”
Section: Introductionmentioning
confidence: 75%
“…Glaucoma following keratoplasty is relatively common, it can appear at any period in the evolution of the graft, it can be difficult to diagnose and to monitor and its treatment can hinder the progress of the transplant [ 50 ]. Simultaneous cataract surgery and keratoplasty could reduce the risk of anterior chamber angle compromise over time as well as in the immediate post-operative period [ 51 , 52 ].…”
Section: Surgical Treatment For Corneal Cloudingmentioning
confidence: 99%